2002
DOI: 10.4049/jimmunol.168.10.5268
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Stromal Cell-Derived Factor-1α Modulates α4β7 Integrin-Mediated Lymphocyte Adhesion to Mucosal Addressin Cell Adhesion Molecule-1 and Fibronectin

Abstract: The interaction between the integrin α4β7 and its ligand, mucosal addressin cell adhesion molecule-1, on high endothelial venules represents a key adhesion event during lymphocyte homing to secondary lymphoid tissue. Stromal cell-derived factor-1α (SDF-1α) is a chemokine that attracts T and B lymphocytes and has been hypothesized to be involved in lymphocyte homing. In this work we show that α4β7-mediated adhesion of CD4+ T lymphocytes and the RPMI 8866 cell line to mucosal addressin cell adhesion molecule-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 61 publications
(54 reference statements)
5
62
0
1
Order By: Relevance
“…These data indicate that also Gai-independent signaling must be involved in CXCL12 enhanced adhesion. In accordance with our findings Wright et al (2002) demonstrated in a study on lymphocytes that PT completely blocked chemotaxis, but the a4b7-dependent adhesion of B and T lymphocytes triggered by CXCL12 was only partially inhibited by PT. In the same work Wright et al reported that inhibition of RhoA activation reduced the upregulation of a4b7-dependent adhesion, suggesting that activation of RhoA is an important step in the signaling leading to increased adhesion.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that also Gai-independent signaling must be involved in CXCL12 enhanced adhesion. In accordance with our findings Wright et al (2002) demonstrated in a study on lymphocytes that PT completely blocked chemotaxis, but the a4b7-dependent adhesion of B and T lymphocytes triggered by CXCL12 was only partially inhibited by PT. In the same work Wright et al reported that inhibition of RhoA activation reduced the upregulation of a4b7-dependent adhesion, suggesting that activation of RhoA is an important step in the signaling leading to increased adhesion.…”
Section: Discussionsupporting
confidence: 93%
“…RhoA has been shown to facilitate both the establishment (Giagulli et al, 2004;Laudanna et al, 1996;Vielkind et al, 2005;Wright et al, 2002) and resolution (Alblas et al, 2001;Smith et al, 2003;Worthylake et al, 2001;Yoshinaga-Ohara et al, 2002) of integrinmediated adhesive events. Whether RhoA promotes adhesion or resolution of adhesion likely depends on which of the numerous signaling pathways that lead to RhoA activation is active.…”
Section: Discussionmentioning
confidence: 99%
“…Because Lsc is a RhoA-specific GEF and RhoA has been implicated in integrinmediated adhesion (Giagulli et al, 2004;Laudanna et al, 1996;Vielkind et al, 2005;Wright et al, 2002) and resolution of adhesion (Alblas et al, 2001;Liu et al, 2002;Smith et al, 2003;Worthylake et al, 2001;Yoshinaga-Ohara et al, 2002), we next assessed how Lsc oligomerization and functional activity correlated with cell morphology and adhesion to integrin ligands. Figure 4A shows that parental and A20 transfectants exhibit a round nonstellate morphology when incubated on BSA-coated substrate.…”
Section: Activation Of Endogenous Lsc Inhibits Cell Polarization and mentioning
confidence: 99%
“…[58][59][60][61][62][63] Rolling and firm adhesion is followed by transendothelial migration across the physical endothelium/extracellular matrix barrier.…”
Section: Trafficking Of Exogenously Administered Stem Cellsmentioning
confidence: 99%